Smart Guard: IoT based Driver Health Monitoring and Safety System - R., Krupa Prasad K; S., Aunsha M; M., Chandan Kumar N; P., Madan Kumar; S, Swarna (IRO Journal on Sustainable Wireless Systems, 2025)
The research presents the design and implementation of an embedded system for monitoring and enhancing driver safety using a combination of health and environmental sensors, along with location and communication modules. The system integrates a heartbeat sensor, sweat sensor, ultrasonic sensor, GPS, and GSM module to provide real-time monitoring and alerts. The heartbeat sensor and sweat sensor track the driver’s physiological conditions, detecting signs of stress or health issues. The ultrasonic sensor monitors the vehicle’s surroundings to prevent collisions. The GPS module tracks the vehicle’s location, and the GSM module enables communication with a central server and the emergency contacts. This system aims to improve driver safety by providing real-time health monitoring, environmental awareness, and emergency response capabilities, representing a significant advancement in the integration of embedded systems and IoT technologies in automotive safety applications.